Analysis of Protection of Women Workers Abroad in the Perspective of Law Number 18 of 2017 Regarding Protection of Indonesian Migrant Workers - Saputera, Yandi (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2022)
Article 27 paragraph (2) of the 1945 Constitution states that Every citizen has the right to work and a decent living for humanity. However, the reality is that the Government as a protector and responsible for the community has not fulfilled the needs of its citizens, especially for women job seekers abroad, even though it is clearly stated in the 1945 Constitution that the people have the right to get a job and a decent life. The results of the study show that Law Number 18 of 2017 has not fully provided protection, especially for Indonesian women workers abroad.